2009
DOI: 10.1021/bi900781u
|View full text |Cite
|
Sign up to set email alerts
|

Significantly Improved Sensitivity of Q-Band PELDOR/DEER Experiments Relative to X-Band Is Observed in Measuring the Intercoil Distance of a Leucine Zipper Motif Peptide (GCN4-LZ)

Abstract: Pulsed Electron Double Resonance (PELDOR)/Double Electron-Electron Resonance (DEER) spectroscopy is a very powerful structural biology tool in which the dipolar coupling between two unpaired electron spins (site-directed nitroxide spin labels) is measured. These measurements are typically conducted at X-band (9.4 GHz) microwave excitation using the 4-pulse DEER sequence and can often require up to 12+ hours of signal averaging for biological samples (depending upon spin label concentration). In this rapid repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 25 publications
2
49
0
Order By: Relevance
“…The huge sensitivity increase at modest microwave (MW) power claimed in later work (35) cannot be reproduced in our hands and is most likely a result of not fully optimizing the X-band measurement. More realistic results were reported later (33,36), although the X-band data taken for comparison still suffer from three times longer pump pulses than would have been been possible with available MW power.…”
Section: Microwave Frequency Bandmentioning
confidence: 74%
“…The huge sensitivity increase at modest microwave (MW) power claimed in later work (35) cannot be reproduced in our hands and is most likely a result of not fully optimizing the X-band measurement. More realistic results were reported later (33,36), although the X-band data taken for comparison still suffer from three times longer pump pulses than would have been been possible with available MW power.…”
Section: Microwave Frequency Bandmentioning
confidence: 74%
“…High field EPR has been driven by many motives, including interest in accessing faster time scales, increased spectral resolution and sensitivity, and the ability to study high-spin species with zero-field splittings too large to be observed at low fields [35]. Pulsed Dipolar Spectroscopy has been implemented at several fields above 0.35 T, which allowed demonstration of improvements in sensitivity [36,37], and offers the capability to perform orientation selective measurements [38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…The origin of this striking result lies at the convergence of the intrinsic increase in signal-to-noise achieved with higher microwave frequencies relative to X-band (9.5 GHz) and the reduced contribution of background intermolecular dipolar coupling in the Nanodisc environment (Ghimire, McCarrick, Budil, & Lorigan, 2009; Zou & McHaourab, 2010). In proteoliposomes, multiple proteins can incorporate into a single liposome, which compresses the bulk spatial distribution of spins from three dimensions to approximately two (Figure 11) (Hilger et al, 2005).…”
Section: Practical Considerations In Sample Preparationmentioning
confidence: 98%